Kombinasi Proses Cold Gelation dan Foam Mat Drying Pada Karakteristik Produk Karagenan - Aji Prasetyoningrum (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Carrageenan is widely used for industrial food as thickening, gelling and stabilizing agents. Gel formation and drying process give effect the quality of carrageenan product. Normally, gel formation of carrageenan by heating and resulting decreasing quality of carrageenan. Ultrasound-assisted cold gelation of kappa carrageenan is new technology for industrial food, and it has several advantages: improvement of rheological properties and product quality, reduce the heat requirement, enhance gel quality, energy efficient, minimizing the using of additional material. Drying is the last step to find carrageenan product. Currently, the carrageenan drying still deals with too long drying time. This because, during the process carrageenan and water forms gel stucture in which hampers the water diffusion to the surface. Foaming agent introduction such as egg white can be considered to break the gel structure and make the drying process being smooth and fast. In general, this study aims to improve the characteristics of carrageenan products through ultrasound-assisted cold gelation and foam mat drying process. The results showed that the gelation treatment (cold gelation) can increase the ultrasonic assisted carrageenan gel strength is 1339,86 g / cm2. This result is higher than the gelation process with heating for 120 minutes (550.40 g / cm2). For 16 minute cold gelation with ultrasonication process give mechanical properties of gel strength (1339,86 g / cm2), hardness (41.75 gf), cohesiveness (0.35), springiness (1.75 mm) and adhesion (0.025 mj). The combination of foam mat drying method can foam created the porous structure in which increased the surface area for drying. As a result, drying time can be shortened. Results showed that the drying time was shortened with the presence of egg white as well as the increase of air temperature. The drying time at air temperature 80 C with 20% egg white was about 20-25 minutes shorter than that of without foam. The data on these results indicate that treatment of ultrasonic waves on carrageenan gel formation and foam mat drying is a potential option that is used to produce carrageenan with high gel strength economically and safely used in food product applications.